Pt doped LaCoO3 perovskite: A precursor for a highly efficient catalyst for hydrogen production from glycerol. (30th January 2016) - Surendar, M.; Sagar, T.V.; Raveendra, G.; Ashwani Kumar, M.; Lingaiah, N.; Rama Rao, K.S.; Sai Prasad, P.S.
Abstract: Au, Ag, Cu, Pt doped cobalt based perovskites (LaCo0.99 X0.01 O3 ) were prepared by co-precipitation method and investigated for their activity in glycerol steam reforming reaction in the temperature range of 400–700 °C and at atmospheric pressure. These catalysts were characterized by ICP- OES, BET surface area, X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), Hydrogen chemisorption, Temperature programmed reduction (TPR), UV–Vis diffuse reflectance spectroscopy (UV–Vis DRS), Scanning electron microscopy (SEM) techniques and CHN analysis. The physico-chemical properties were compared for the fresh, reduced and spent catalysts. The Pt-doped catalyst displayed the best hydrogen yield (78.4%) at 96.0% conversion of glycerol. The superior performance of the catalyst was explained in terms of the dispersion of the cobalt metal. The catalyst was also found to be stable during the time on stream analysis due to low carbon formation. Graphical abstract: Pt promoted LaCoO3 perovskite precursor was efficient in producing the highly active cobalt species during reduction. The nano-cobalt particles generated offered the best hydrogen yield and minimized coke formation giving longer catalyst life. Highlights: Pt doped LaCoO3 generates a highly efficient catalyst for glycerol steam reforming. Octahedral Co 3+ species are easily reducible at lower temperature. The superior catalytic activity of LaCo0.99 Pt0.01 O3 is due to high Co dispersion. Co particles of 1.8 nm could be obtained after reduction. Smaller particles are highly resistant to coke formation.